The Seriousness of Mistakes and the Benefits of Getting it Right: Symmetries and Asymmetries in the Ethics of Epistemic Risk Management - Wilholt, Torsten (Kennedy Institute of Ethics journal, 2024)
Scientists have to make trade-offs between different types of error risks when making methodological decisions. It is now widely recognized (and not disputed in this article) that in doing so they must consider how serious the consequences of each error would be. The fact that they must also consider the potential benefits of getting it right is not equally recognized (and explicitly rejected by Heather Douglas). In this article, I argue that scientists need to do both when managing epistemic risks. At the same time, I acknowledge that in some cases it intuitively seems as if considering the consequences of possible errors carries greater moral weight. I explain this intuition by arguing that in these cases the contrast between the seriousness of mistakes and the benefits of getting it right can be linked to the moral asymmetry between action and omission. I examine various reasons that might justify a stronger weighting of the consideration of the consequences of errors in light of the action-omission asymmetry. I conclude that for all but some exceptional cases, such asymmetrical consideration is not called for.